Species composition, stand characteristics, aboveground biomass, and carbon stock of mangroves in Panabo Mangrove Park, Philippines - JEMER A. ALIMBON; MARK RONALD S. MANSEGUIAO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Alimbon JA, Manseguiao MRS. 2021. Species composition, stand characteristics, aboveground biomass, and carbon stock of mangroves in Panabo Mangrove Park, Philippines. Biodiversitas 22: 3130-3137. Mangrove ecosystems have been recognized for their roles in climate change mitigation through their carbon sequestration capacity. However, information on the ecology and carbon stock of mangroves is limited. Thus, this study assessed the species composition, stand characteristics, aboveground biomass, and carbon stock of mangroves in Panabo Mangrove Park, Panabo City, Davao del Norte, Philippines. Data for vegetation analysis and biodiversity assessment were collected using transect line plots method. Meanwhile, aboveground biomass estimation was conducted using nondestructive method. Twenty plots with size of 10 m x 10 m each were established to account for the stand characteristics and aboveground biomass of mangroves. Species composition data identified five species from four families. Avicennia marina was the most important species with an importance value of 153.33%. Stand structure analysis revealed a basal area of 14.65 m² ha?¹ and a mean density of 11835 stems ha?¹. Biodiversity indices indicated very low species diversity (H’ = 1.027), low species richness (R = 0.5148) and less even distribution of species (J = 0.6383). Using allometric equation, the aboveground biomass was 77.45 Mg ha?¹ with an estimated stored carbon of 37.18 Mg ha?¹ and sequestration potential of 136.44 Mg CO?ha?¹. These baseline data demonstrate that the area can store and sequester potential amounts of carbon and carbon dioxide, respectively, despite the low diversity.